ANALYSIS OF INTEGRATED BUILT-IN GRAPHICS PROCESSORS - Романюк, Олександр; Мазур, Вадим; Тітова, Наталія; Коробейнікова, Тетяна; Глоба, Анна (SWorldJournal, 2023)
The paper analyzes the existing built-in graphics processors in central processors. The work of various types of embedded graphics processors in technological processes is considered